2019
DOI: 10.1007/s11270-019-4189-7
|View full text |Cite
|
Sign up to set email alerts
|

Pentachlorophenol Removal from Water by Soybean Peroxidase and Iron(II) Salts Concerted Action

Abstract: Soybean peroxidase (SBP) has been employed for the treatment of aqueous solutions containing pentachlorophenol (PCP) in the presence of hydrogen peroxide at pH range 5-7. Reaction carried out with 1 mg/L of PCP, 4 mg/L of H2O2 and 1.3 x 10 -9 M of SBP, showed a fast initial elimination of PCP (ca. 30% in 20 min), but the reaction does not go beyond the removal of 50% of the initial concentration of PCP.Modification in SBP and PCP amounts did not change the reaction profile and higher amounts of H2O2 were detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…For the extraction of soybean peroxidase (SBP) (Tolardo et al, 2019 ), the seeds were peeled, and the obtained hulls were stored at −12°C until use. SBP was extracted and purified by a process based on a previously published method (Calza et al, 2016 ): 100 g of soybean hulls were ground in a mortar, added to 600 mL of phosphate buffer (0.025 M, pH 7) and left under stirring for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…For the extraction of soybean peroxidase (SBP) (Tolardo et al, 2019 ), the seeds were peeled, and the obtained hulls were stored at −12°C until use. SBP was extracted and purified by a process based on a previously published method (Calza et al, 2016 ): 100 g of soybean hulls were ground in a mortar, added to 600 mL of phosphate buffer (0.025 M, pH 7) and left under stirring for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies of SBP uses for industrial wastewater treatment in the literature, as well as SBP extraction and purification processes [10][11][12][13][14][15][16][17]. Over the years some of the limitations and advancements in the field have been presented, considering aspects such as cost, use of additives for increased enzyme economy, enzyme recycling and studies already completed on industrial wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the degradation products can be identified directly [20,21], since the products usually show different toxicity than the reagents [11]. The most recent study of phenolic compound removal using SBP was in the treatment of aqueous solutions containing pentachlorophenol [17], based on previous studies of TCP degradation [18]. Besides, it was observed that the removal of pentachlorophenol was not complete, maybe because of the interference of intermediates or reaction products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors showed the effectiveness of SBP in the oxidation of chlorophenols [14][15][16][17][18]. The ability of SBP in the degradation of 2,4,6-trichlorophenol (TCP) was previously studied by Calza et al [19] using composite material under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%